Fire damaged ultra-high performance concrete (UHPC) under coupled axial static and impact loading. (February 2022) - Liu, Kai; Wu, Chengqing; Li, Xibing; Tao, Ming; Li, Jun; Liu, Jian; Xu, Shenchun
Abstract: The load bearing structural components such as columns could experience axial static loads during the service life. High temperature induced by fire would have a significant detrimental impact on the mechanical properties of concrete materials. The structure could be severely damaged as the column was simultaneously loaded by other impact loads. In this study, the behavior of fire damaged ultra-high performance concrete (UHPC) with a compressive strength of 128.3 MPa under coupled axial static and impact loading was studied. UHPC specimens were heated to the target temperatures (250, 500 and 750 °C) in an electric furnace and then naturally cooled down to room temperature. The results demonstrated that the P-wave velocity and compressive strength of the heated-cooled treatment UHPC degraded significantly as the target temperature exceeded 250 °C. The impact tests were then conducted on the heated-cooled treatment UHPC specimens with axial static compression. The experimental results indicated that the axial static compression could enhance the dynamic mechanical properties such as compressive strength and elastic modulus in the elastic phase and weaken the dynamic mechanical properties in the plastic phase. In addition, the dynamic increase factor (DIF) of UHPC exhibited an increase with the temperature. The UHPC specimen could withstand a temperature of 250 °C, but lost most of its strength at temperatures of 500 and 750 °C. Thus, the axially loaded static force accelerated the failure of the specimen after being heated to above 250 °C.